The Narrative Dimension of Symbolic Violence in EducationalInstitutions - Jiménez-Herrera, Julio (Emerging Trends in Education, 2026)
Language, in general, is undoubtedly the quintessential and most ubiquitous vehicle through which we communicate, exchange ideas, reach agreements, or disagree about things in the world. Narrative language, in particular, is the vehicle of everyday life through which we exchange (in interaction with others) socially produced and constructed meanings. On the other hand, symbolic violence is that which does not literally strike, but nevertheless leaves its mark on those upon whom the will of another is imposed (through narrative), those who impose their cultural meanings in the pursuit of their fines. The purpose of this paper is to offer a theoretical reflection on the impact of symbolic violence that occurs in educational institutions (at any level of education), while also exposing how, from the moment a child, young person, or adult enters its doors, the school renders them unequal, and this inequality generates asymmetrical spaces in which symbolic violence occurs. Being a student is not the same as being a teacher, assistant principal, or principal. Narrative, whether written or spoken, plays an important role in invisibly and inexorably channeling symbolic violence in educational systems.